Leucine Zipper 4 Autoantibody: A Novel Germ Cell Tumor and Paraneoplastic Biomarker. Issue 5 (28th February 2021) - Dubey, Divyanshu; Kryzer, Thomas; Guo, Yong; Clarkson, Benjamin; Cheville, John C.; Costello, Brian A.; Leibovich, Bradley C.; Algeciras‐Schimnich, Alicia; Lucchinnetti, Claudia; Hammami, M. Bakri; Knight, Andrew M.; Howe, Charles; et al.
Abstract : Objective: This study was undertaken to describe a novel biomarker of germ cell tumor and associated paraneoplastic neurological syndrome (PNS). Methods: Archival sera from patients with germ cell tumor–associated PNS were evaluated. We identified a common autoantigen in a human testicular cancer cell line (TCam‐2) by Western blot and mass spectrometry. Its identity was confirmed by recombinant‐protein Western blot, enzyme‐linked immunosorbent assay (ELISA), and cell‐based assay. Autoantibody specificity was confirmed by analyzing assorted control sera/cerebrospinal fluid. Results: Leucine zipper 4 (LUZP4)–immunoglobulin G (IgG) was detected in 28 patients' sera, 26 of whom (93%) were men. The median age at neurological symptom onset was 45 years (range = 28–84). Median titer (ELISA) was 1:300 (1:50 to >1:6, 400, normal value < 1:50). Coexistent kelchlike protein 11–IgG was identified in 18 cases (64%). The most common presenting phenotype was rhombencephalitis (17/28, 61%). Other presentations included limbic encephalitis (n = 5, 18%), seizures and/or encephalitis (n = 2, 7%), and motor neuronopathy/polyradiculopathy (n = 4, 14%). The most common malignancy among cancer‐evaluated PNS patients was seminoma (21/27, 78%). Nine of the 21 seminomas detected by whole‐body fluorodeoxyglucose positron emission tomography scan (43%) were extratesticular. Both female patients had ovarian teratoma. Regressed testicular germ cell tumors were found in 4 patients. Exposure of T‐cell–dendritic‐cell cocultures from chronic immunosuppression‐naïve LUZP4‐IgG–seropositive patients to recombinant LUZP4 protein evoked a marked increase in CD69 expression on both CD4+ and CD8+ T cells when compared to vehicle‐exposed and healthy control cultures. Interpretation: LUZP4‐IgG represents a novel serological biomarker of PNS and has high predictive value for germ cell tumors. The demonstrated antigen‐specific T‐cell responses support a CD8+ T‐cell–mediated cytotoxic paraneoplastic and antitumor potential. ANN NEUROL 2021;89:1001–1010